2008
DOI: 10.1007/s10750-008-9329-9
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of free-swimming Annelida in four Dutch wastewater treatment plants in relation to process characteristics

Abstract: Free-swimming Annelida occasionally occur in very high densities in WWTPs (WasteWater Treatment Plants) and are nowadays applied for waste sludge reduction, but their growth is uncontrollable. In order to get more insight in the population dynamics of these free-swimming Annelida, and relate their presence to process characteristics, nine ATs (Aeration Tanks) of four Dutch WWTPs were regularly sampled over a 2.5-year period. For each species, peak periods in worm population growth were defined and population d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Various species of Naidinae and Pristininae can disperse actively in the water column (Learner et al, 1978) and can thus more easily colonize different habitats, including decomposing organic material. In contrast, the Tubificinae live in direct contact with the substrate (Elissen et al, 2008) and are slow colonizers (Levin et al, 1996). In a river from a temperate region, Chauvet et al (1993) observed high biomass and regular occurrence of Tubificinae in decomposing willow leaves, which resulted in highly fragmented leaf litter, suggesting that these oligochaetes can increase the fragmentation of leaves by their movement and feeding on leaf parenchyma cells and the associated bacteria.…”
Section: Oligochaetesmentioning
confidence: 99%
“…Various species of Naidinae and Pristininae can disperse actively in the water column (Learner et al, 1978) and can thus more easily colonize different habitats, including decomposing organic material. In contrast, the Tubificinae live in direct contact with the substrate (Elissen et al, 2008) and are slow colonizers (Levin et al, 1996). In a river from a temperate region, Chauvet et al (1993) observed high biomass and regular occurrence of Tubificinae in decomposing willow leaves, which resulted in highly fragmented leaf litter, suggesting that these oligochaetes can increase the fragmentation of leaves by their movement and feeding on leaf parenchyma cells and the associated bacteria.…”
Section: Oligochaetesmentioning
confidence: 99%
“…Initially, research focused on extending the food web with aquatic worms that naturally occur in WWTPs. However, this process proved impossible to control and high worm densities could not be maintained [3,4]. Further research therefore focused on separate worm reactors in which conditions could be optimized for the worms [2].…”
Section: Waste Sludge Production From Waste Water Treatmentmentioning
confidence: 99%
“…They are a common part of the invertebrate fauna, especially in eutrophic habitats, and representatives of the group are frequently subject to ecological studies (e.g. Löhlein, 1996; van Duinen et al ., 2006; Verdonschot, 2006; Elissen et al ., 2008). Some species are cosmopolitan, others show a delimited area of distribution, and the genus appears to be more abundant in temperate zones than in tropical or subtropical regions (Sperber, 1948).…”
Section: Introductionmentioning
confidence: 99%